Reading the Text of Suwaray Ilkhanizadeh’s Poem (Shar) from the Perspective of the Ecocriticism Method - Ibrahim Mohammed Ibrahim (Zanco Journal of Humanity Sciences)
The present research is titled “Reading the Text of Suwaray Ilkhanizadeh’s Poem (Shar) from the Perspective of the Ecocriticism Method.” Due to the urgent global environmental crisis and its severe threats to human existence and the natural environment, ecological criticism has become more popular as a critical contemporary approach in the latter half of the twentieth century. Ecological critics have endeavored to transform literature into a platform for combating the challenges posed to the ecosystem and contributing to alleviating environmental issues. This study examines Ilkhanizadeh’s poem (Shar) as an exemplar, which notably addresses ecological themes concerning the environment and human life. Its primary objective is to reveal Ilkhanizadeh’s ecological viewpoints concerning the urban environment, examining the dynamic relationship between human culture, society, and the natural surroundings. By delving into the poem’s ecological elements, this research raises awareness about the environmental crises resulting from prevalent urban systems and disciplinary practices.